Penyuluhan Tentang Demam Berdarah (DBD) dan Tanaman Pengusir Nyamuk Di Lingkungan Kecamatan Manggala Kota Makassar - Muawanah Muawanah; Siti Mu'tamirah; Tuty Widyanti (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
Manggala District is one of the sub-districts in Makassar City which often faces cases of Dengue Fever. Dengue fever is a disease transmitted through the bite of the Aedes aegypti mosquito. The breeding of Aedes Aegypti is increasing due to the increasingly crowded conditions of buildings and housing. These mosquitoes not only live in dirty water environments, but also in clean water such as bathtubs, water reservoirs, and others. Some community members still have limited knowledge and understanding of effective ways of dealing with dengue cases, as well as the use of plant species that can be used to repel mosquitoes. The purpose of the service is to increase the knowledge and understanding of the community about dengue fever and the use of mosquito repellent plants. The extension method is the presentation by the extension team, the discussion stage, and the evaluation stage. The results show an increase in public knowledge and understanding of dengue disease and the use of mosquito repellent plants. The conclusion is that the community finally knows the dangers of dengue disease and knows the types of mosquito repellent plants.